2022
DOI: 10.53730/ijhs.v6ns6.10874
|View full text |Cite
|
Sign up to set email alerts
|

Coaching commitment and physical development of student-athletes from various public schools in Angeles City, Pampanga, Philippines

Abstract: This present study aims to determine the relationship between coaching commitment and physical development of student-athletes from various public schools in Angeles City, Pampanga, Philippines. Respondents on the study are student-athletes from Senior High School Public Schools from Grade 11 and 12. Descriptive statistics such as Mean and Standard Deviation were used to describe the level of coaching commitment and physical development according to categories, and Pearson Product Moment Correlation Coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Moreover, the participants for the study were selected via Purposive Sampling. This non-probability sampling technique is used because of the participants' qualities that are needed and fitted for this investigation (Lobo, 2022). One hundred sixteen (116) students voluntarily participated in the investigation, and all responses were accepted for analysis.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the participants for the study were selected via Purposive Sampling. This non-probability sampling technique is used because of the participants' qualities that are needed and fitted for this investigation (Lobo, 2022). One hundred sixteen (116) students voluntarily participated in the investigation, and all responses were accepted for analysis.…”
Section: Participantsmentioning
confidence: 99%
“…Moreover, to describe the participants' responses, descriptive statistics such as Mean (M) and Standard Deviation (SD) were used via IBM SPSS version 27. For the facilitation of the interpretation of obtained data, a point-scale interpretation was adapted from Lobo et al (2022) to describe per item response which is shown in Table 3.…”
Section: Data Analysis Quantitative Phasementioning
confidence: 99%